DEVELOPMENT OF INNOVATIVE BEHAVIOR OF FUTURE QUALIFIED WORKERS IN VOCATIONAL EDUCATION INSTITUTIONS IN WAR AND POST-WAR TIMES (Innovative professional education, 2024)
It is substantiated that the constant search and introduction of innovations for the educational activities of our country becomes a guarantee of the functioning and development of education in the conditions of the war and post-war times. The innovative activity of vocational education institutions is considered in the context of three spheres of training of the future skilled worker: personal, activity and social. The author's training course "Innovative behavior" is characterized.
Keywords: professional education, skilled worker, innovative activity of a professional education institution, innovative behavior